Body atlas ([United States] Discovery Communications, 1994)
The Brain shows graphic images of the brain and how it controls the rest of the body. In the womb views the human body as it forms in the womb.
The brain (24 min.) -- In the womb (28 min.)
VHS.
Produced by Pioneer Productions for the Learning Channel.
Segments from discs 1 and 5 of the Body atlas series.
Thelma Rumsey, director ; Nigel Henbest, Thelma Rumsey, writers ; Nigel Henbest, producer.
Keywords: Brain -- Growth; Fetus -- Growth; Human anatomy; Human physiology; Body, Human